2005
DOI: 10.1042/bj20041835
|View full text |Cite
|
Sign up to set email alerts
|

Activation and assembly of the NADPH oxidase: a structural perspective

Abstract: The NADPH oxidase of professional phagocytes is a crucial component of the innate immune response due to its fundamental role in the production of reactive oxygen species that act as powerful microbicidal agents. The activity of this multi-protein enzyme is dependent on the regulated assembly of the six enzyme subunits at the membrane where oxygen is reduced to superoxide anions. In the resting state, four of the enzyme subunits are maintained in the cytosol, either through auto-inhibitory interactions or thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
528
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(547 citation statements)
references
References 200 publications
(273 reference statements)
13
528
0
6
Order By: Relevance
“…In addition, enzymes such as lipoxygenases may also generate O 2 Ϫ . NOX has been implicated in several studies as the source of O 2 Ϫ in hypertension, atherosclerosis, and heart failure (5,11,17,32,46).The hypothesis of the present study is that the primary source of O 2 Ϫ during reverse flow stems from the NOX system. We tested this hypothesis by inhibiting various pathways while assessing the nitrite production and the degree of vasodilation.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, enzymes such as lipoxygenases may also generate O 2 Ϫ . NOX has been implicated in several studies as the source of O 2 Ϫ in hypertension, atherosclerosis, and heart failure (5,11,17,32,46).The hypothesis of the present study is that the primary source of O 2 Ϫ during reverse flow stems from the NOX system. We tested this hypothesis by inhibiting various pathways while assessing the nitrite production and the degree of vasodilation.…”
mentioning
confidence: 70%
“…First, the saccharide chains that are attached to glycosylation sites found on the NOX homologue subunit which has six transmembrane helixes may be implicated (17,50). These chains may transmit reverse shear to the NOX homologue, causing increased O 2 Ϫ production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The production of superoxide by microglia occurs primarily by NADPH oxidase (NOX), of which several isoforms have been characterized. 23,24 Of note, glucose availability can be rate-limiting for NADPH production, and thus for superoxide production, and this provides a mechanism by which hyperglycemia can exacerbate injury during ischemia or inflammation. 25,26 Recent work has shown that microglia can potentiate injury to blood-brain barrier constituents (astrocytes and endothelial cells) via NOX-mediated superoxide in cell culture models of ischemia.…”
Section: Superoxide Productionmentioning
confidence: 99%
“…The cytosolic components translocate to the membrane on neutrophil activation to form a functional oxidase complex with cytochrome b 558 . 60,61 To determine the level of expression of the NADPH oxidase subunits, quantitative Western immunoblot analysis was performed in WT and LFKO neutrophils. No significant difference in the levels of p22 phox , p40 phox , p47 phox , p67 phox , or gp91 phox were detected in the two groups ( Figure 5) indicating that the abnormal PMA-stimulated oxidative burst response observed in LFKO neutrophils is not because of altered expression of the NADPH oxidase subunits in these mice.…”
Section: Normal Expression Of Nadph Oxidase Components In Lfko Neutromentioning
confidence: 99%